Effectiveness of VR Technology Integrated with Flipped Classroom Teaching Model for College Students’ Psychological Health Education - Wu, Di; Sitthiworachart, Jirarat; Ratanaolarn, Thanin (My University, 2026)
Although both virtual reality (VR) technology and the flipped classroom teaching model have shown individual promise in educational settings, there is limited empirical research evaluating their combined effectiveness for enhancing college students’ psychological health education. This is especially important as depression and anxiety are increasingly prevalent among Chinese college students. To fill this gap, this study aimed to investigate the effectiveness of VR technology integrated with the flipped classroom teaching model on reducing students’ depression and anxiety levels and enhancing student learning achievement. The researcher used a two-group pretest and posttest experimental design to conduct the experiment, while Zung’s self-rating depression and anxiety scales were used to test participants’ depression and anxiety levels, and learning achievement was tested by the standardized test of psychological health education in Anhui University of Science and Technology. The screening sampling method has been used in the participant selection process to select those who were on a mild depression and anxiety level. 80 participants from Anhui University of Science and Technology were involved in a 10-week experiment. MANOVA has been used to analyze the obtained data. The research findings showed all of the P-values <0.001, indicating that there was a positive influence of VR technology integrated with the flipped classroom teaching model on student depression status, anxiety status, and learning achievement. This study suggested that adopting VR-enhanced flipped classroom practices in psychological health education holds promise for improving both student mental health and academic outcomes, with important implications for curriculum development and educational policy in higher education settings.
Keywords: anxiety level; depression level; flipped classroom; learning achievement; psychological health education; VR technology